The Role of Plyometric Training in Improving Explosive Power in Sprinters: A Qualitative Analysis - Bastholm , Mathias; Olsen, Geoffrey (International Journal of Sport Studies for Health, 2024)
Objective: The objective of this study was to explore the role of plyometric training in enhancing explosive power among sprinters.Methods and Materials: This qualitative research employed semi-structured interviews to gather data from 17 sprinters aged 18 to 30 years, with at least three years of competitive experience. Participants were recruited from local athletic clubs and universities. Data collection continued until theoretical saturation was achieved, ensuring a comprehensive understanding of the impact of plyometric training. Thematic analysis was used to identify and analyze patterns within the data, providing detailed insights into the participants' experiences and perceptions.Findings: The study revealed significant physical improvements attributed to plyometric training, including enhanced muscle strength, increased speed, improved jumping ability, and reduced injury risk. Psychological benefits such as increased confidence, enhanced motivation, and improved mental resilience were also noted. Participants reported a better training experience with diverse and efficient routines, improved technique understanding, and strong peer support. Performance outcomes showed notable improvements in competition results, skill application, and recovery times. These findings align with existing literature, confirming the comprehensive benefits of plyometric training for sprinters.Conclusion: Plyometric training significantly enhances explosive power and overall performance in sprinters. The physical, psychological, and performance-related benefits make it a crucial component of athletic training programs. Despite limitations such as the small sample size and reliance on self-reported data, the study provides valuable insights into the multifaceted advantages of plyometric exercises.